Micropolar nanoparticles flow on a stretching/shrinking sheet with multiple slips - Mahabaleshwar, U. S.; Vanitha, G. P.; Perez, L. M.; Öztop, Hakan Fehmi (Elsevier, 2024)
The purpose of this paper is to examine the flow of micropolar fluid containing ternary nanoparticles, with multiple slips over a stretching/shrinking sheet. Also, the influences of internal radiation and with the first order chemical reaction are examined to study the fluid properties. Mathematical modeling for the defined problem is framed and yields coupled nonlinear PDEs which are then reduced to nonlinear ODEs by choosing suitable similarity variables. The resulting ODEs are solved by analytical technique and solution is represented as an incomplete gamma function and a hypergeometric function. The regulating parameters, such as Eringen parameter, chemical reaction parameter, inverse Darcy number, Prandtl number and radiation parameter impact are examined for the profiles of velocity, microrotation, energy and concentration of the fluid through graphs. Furthermore, the skin friction drag of the defined flow is also discussed. This investigation reveals the existence of multiple solutions for the case of shrinking and for the case of stretching it shows a unique solution. Also, the tri-hybrid nanofluid flow velocity is found to increase and decrease for the first and second solutions respectively. The velocity, energy and concentration of the flow are found to decrease due to slip conditions.
Keywords: Micropolar fluid; Multiple slips; Chemical reaction; Nanoparticles; Stretching/shrinking sheet; Analytical solution